APPOINTING NON MUSLIM LEADERSHIP BASED ON FIQH SIYASAH PERSFECTIVE AND THE IMPLEMENTATION IN INDONESIA - Muhammad Ramadhan; Bambang Saputra; Adhia Nugraha (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
This paper is a literature study and field study, the theme raised was appointed non-Muslim leaders from the perspective of Fiqh Siyasah and the implementation in Indonesia. There are three questions: first, how is the concept of non-Muslim leaders in Islamic studies? Second, how is to appoint non-Muslim leaders in the Fiqh Siyasa perspective? third, and how is the implementation in Indonesia? By using content analysis to explain the first question, about how is the concept of non-Muslim leaders in Islamic studies and also the second question, how is to raise non-Muslim leaders in the perspective of Fiqh Siyasah, and also field approach to explain it’s implementation in Indonesia, the results of this paper are: first, knowing the leaders' concepts of non-Muslims in Islamic studies, second, knowing appointed non-Muslim leader in the Fiqh Siyasa perspective., third, knowing the implementation of non-Muslim leaders in Indonesia. Keywords. Non-Muslim Leaders, Fiqh Siyasah, Implementation in Indonesia